Chiaravalle 1350: Time consciousness between Jubilees and Emperor (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
A collection of depositions dating back to the winter 1350 enables us to know mechanisms of memory, perception and representation of time lived by six people living in the country of Milan between 13th and 14th century. The depositions show that historical breaks which were used to place personal memories exceeded the local boundaries (Chiaravalle in particular), referring to universal contexts: «time of Church» as well as «time of Empire». The depositions are framed by Jubilees and imperial descents - events of universal significance marking collective imagination at all levels.
Keywords: Chiaravalle; Middle Ages; Memory; Lived time; Landscape; Jubilee